MBOAT7-driven phosphatidylinositol remodeling promotes the progression of clear cell renal carcinoma - Chase K.A. Neumann; Daniel J. Silver; Varadharajan Venkateshwari; Renliang Zhang; C. Alicia Traughber; Christopher Przybycin; Defne Bayik; Jonathan D. Smith; Justin D. Lathia; Brian I. Rini; J. Mark Brown (Molecular Metabolism, 2020)
Objective: The most common kidney cancer, clear cell renal cell carcinoma (ccRCC), is closely associated with obesity. The “clear cell” variant of RCC gets its name from the large lipid droplets that accumulate in the tumor cells. Although renal lipid metabolism is altered in ccRCC, the mechanisms and lipids driving this are not well understood. Methods: We used shotgun lipidomics in human ccRCC tumors and matched normal adjacent renal tissue. To assess MBOAT7s gene expression across tumor severity, we examined histologically graded human ccRCC samples. We then utilized genome editing in ccRCC cell lines to understand the role of MBOAT7 in ccRCC progression. Results: We identified a lipid signature for ccRCC that includes an increase in arachidonic acid-enriched phosphatidylinositols (AA-PI). In parallel, we found that ccRCC tumors have increased expression of acyltransferase enzyme membrane bound O-acyltransferase domain containing 7 (MBOAT7) that contributes to AA-PI synthesis. In ccRCC patients, MBOAT7 expression increases with tumor grade, and increased MBOAT7 expression correlates with poor survival. Genetic deletion of MBOAT7 in ccRCC cells decreases proliferation and induces cell cycle arrest, and MBOAT7−/− cells fail to form tumors in vivo. RNAseq of MBOAT7−/− cells identified alterations in cell migration and extracellular matrix organization that were functionally validated in migration assays. Conclusions: This study highlights the accumulation of AA-PI in ccRCC and demonstrates a novel way to decrease the AA-PI pool in ccRCC by limiting MBOAT7. Our data reveal that metastatic ccRCC is associated with altered AA-PI metabolism and identify MBOAT7 as a novel target in advanced ccRCC. Keywords: Clear cell renal carcinoma, Lipid, Phosphatidylinositol, Metabolism